Biosynthesis of CuO nanoparticles using Mimosa hamata extracts. (2021) - Sackey, J.; Razanamahandry, L.C.; Ntwampe, S.K.O.; Mlungisi, N.; Fall, A.; Kaonga, C.; Nuru, Z.Y.
Abstract: Green chemistry with its objective of overcoming chemical hazards is an attractive method of synthesising nano-metallic oxides. This study reports for the first time, the green synthesis and characterization of CuO nanoparticles using Mimosa hamata flower extracts as reducing agents. The X-ray diffraction (XRD), Attenuated total reflection-Fourier transform infrared (ATR/FTIR), and Photoluminescence (PL) spectroscopy analyses were subsequently performed post-annealing at 500 °C in air, confirming the formation of Tenorite- based centered monoclinic CuO. The average particle size obtained from the XRD for both annealed and as-preapred samples varied with the concentrations. The energy band gap calculated from the diffuse reflectance was 1.5 eV, 1.3 eV, and 1.2 eV for the different cupric acetate concentrations used, i.e. 0.5, 1.0 and 1.5 g per 10 mL, respectively. The photoluminescence properties obtained at ambient temperature gave emission peaks at 417 and 437 nm which were ascribed to the near-band-edge emission peak of CuO. Furthermore, Anti-bacterial studies were performed on both the as-prepared and annealed CuO for direct application purposes. The as-prepared CuO (liquid form) was demonstrated to have better antimicrobial activity than the CuO powder formed after annealing at 500 °C.